Propriedade de quem?: proteção social e confisco tributário no Brasil - Marina Soares Marinho (2024)
This thesis rests on the integrity of the constitutional system to deduce, from the systematic interpretation of its content, that property has a more comprehensive concept than traditionally considered by the tax system (income) and that this has definitive implications on the assessment of confiscation and the evaluation of the tax-paying capacity of Brazilians. Tax confiscation occurs when taxation reaches the existential minimum, a situation in which there is no capacity to contribute. This means that confiscatory taxation reaches into private property, which includes access to social protection, of taxpayers who do not have access to fundamental rights related to human dignity.